EVALUASI ON GOING DANA ALOKASI KHUSUS FISIK BIDANG PENDIDIKAN DALAM MASA PANDEMI CORONA VIRUS DISEASE-19 BERBASIS INTELLIGENCE MEDIA MANAGEMENT (IMM) - Andi Setyo Pambudi (Jurnal Kebijakan Pemerintahan, 2021)
The DAK allocation for education is always available every year with a large budget compared to other fields, even during the COVID-19 pandemic. At the local government level, education is a priority. Local government funding needs through the Physical DAK are expected to be in line with the wishes of the central government. The implementation of the Physical DAK in the Education Sector as a funding instrument to the regions in 2020 faced the challenges of the COVID-19 outbreak in March which affected the optimization of the development process. The government took the option of a relaxation policy to facilitate the implementation of DAK in the field. This requires an ongoing evaluation using the current state method as input for planning for the following year. The implementation of the Physical DAK and all its menus encourages the importance of information on achievements and field constraints to remain current and scientifically accountable. The study aims to present obstacles, information, and matters related to the implementation of the Physical DAK in the Education Sector in 2020 during the COVID-19 pandemic as a response to current conditions without having to visit. The method used is a literature study and statistical analysis based on big data as an option that is relevant to the current situation to provide a basis for providing development planning recommendations. Big data analysis utilizes Intelligence Media Management (IMM) tools to see public perceptions regarding the implementation of the Physical DAK in the Education Sector during the COVID-19 pandemic. The results showed that as much as 40 percent of the news related to the DAK in the Education Sector during the COVID-19 Pandemic in the form of positive sentiment, 17 percent negative, and 43 percent neutral sentiment. In the negative sentiment, the news that was highlighted was the demand that DAK managers be able to immediately complete construction according to technical instructions in the field. The top issue of DAK Education news as input for development improvement is about the findings of discrepancies in the basic data of education (DAPODIK) with facts on the ground which in turn has an impact on the inaccurate target of DAK recipients. Keywords: Big Data, DAK, Evaluation, Education